Answer:
0
Step-by-step explanation:
7 + 5 - 15 -(-3)
=> 12 - 15 + 3
=> 12 - 12
=> 0
x5 - 10x2 - 8
—————————————
x - 2
Answer:
b^2-4b+3=0
b²-3x-b+3=0
b(b-3)-1(b-3)=0
(b-3)(b-1)=0
either
b=3 or b=1
.
2n^2 + 7 = -4n + 5
2n²+4n+7-5=0
2n²+4n+2=0
2(n²+2n+1)=0
(n+1)²=0/2
:.n=-1
.
x - 3x^2 = 5+ 2x - x^2
0=5+ 2x - x^2-x +3x^2
0=5+x+2x²
2x²+x+5=0
comparing above equation with ax²+bx +c we get
a=2
b=1
c=5
x={-b±√(b²-4ac)}/2a ={-1±√(1²-4×2×5)}/2×1
={-1±√-39}/2
Answer:
x = 72 / 85
Step-by-step explanation:
x -6/7=-x/84
x + x/84 = 6/7
84/84x + 1/84x = (12*6) / (12*7)
85/84x = ( 72 ) / ( 84 )
85/84x = 72 / 84
Multiply left and right from the = sign by 84/85 and you do that so you get a division ON THE LEFT SIDE that equals as 1... See how it works:
84/85 * { 85/84 } * x = 84/85 * { ( 72 ) / ( 84 ) }
{ (84 * 85) / ( 85 * 84) } * x = ( 84 * 72 ) / ( 85 * 84 )
(7140) / ( 7140) * x =. ( 6048 ) / ( 7140)
x = 6048 / 7140
x = 72 / 85